The Comparison of the Tropical Cyclone Number Over the Western North Pacific Between Summer and Autumn - Liu, Jia; Chen, Zhifan; Li, Jiang (Frontiers in Earth Science, 2020)
Based on the observational evidences that the tropical cyclones (TCs)number in the western North Pacific (WNP) in autumn is more than that in summer, this study mainly compares the disturbance of some conditions that associated with the formation of TCs between the two seasons. Results show that the most of the distributions of the disturbance field of atmospheric dynamic factor are similar, while the unique feature of the upper level geopotential height/vortex anomaly over east Asia/western Pacific sector varies greatly and may play the important role in generating more TCs in autumn. Further analyses indicate that the high-pressure/anticyclonic anomaly in autumn is originated from the north tropical Atlantic Ocean. When a cold sea surface temperature (SST) anomaly appears in north tropical Atlantic, a Rossby wave train over Eurasia continent could be induced which then leads a favorable condition for TC genesis over east Asia/western Pacific sector at upper troposphere, resulting in more WNP TCs in autumn.